EUROLAB: A multidimensional labour supply-demand model for EU countries - Edlira Narazani; Ugo Colombino; Bianey Palma (European Commission, Joint Research Centre (JRC), 2021)
This paper describes EUROLAB, a labour supply-demand microsimulation model that relies on EUROMOD, the static microsimulation model for the European Union countries. EUROLAB is built on a multidimensional discrete choice model of labour supply and accounts for involuntary unemployment. The model estimates individual changes in supplied hours of work and participation as a reaction to a hypothetical or real taxtransfer reform, often referred to in the literature as "second-order" effects. Furthermore, the model allows for the demand-side effects of a labour market that, depending on how elastic it is, would lead to a different labour supply when the market reaches its equilibrium. The model is unique in covering 27 countries under the same specification of preferences, opportunity set representation and the same concept of income and working hours. We illustrate the usefulness of the model by showing several examples of EUROLAB, using both the one-dimensional and multidimensional versions. Potential extensions of the model are also discussed in the paper.
Keywords: J22; J23; J640; H310; 330; Behavioural Models; Discrete Choice Modelling; Labour supply; Labour market equilibrium